2017
DOI: 10.1530/rep-17-0358
|View full text |Cite
|
Sign up to set email alerts
|

LEM-domain proteins are lost during human spermiogenesis but BAF and BAF-L persist

Abstract: During spermiogenesis the spermatid nucleus is elongated, and dramatically reduced in size with protamines replacing histones to produce a highly compacted chromatin. After fertilisation, this process is reversed in the oocyte to form the male pronucleus. Emerging evidence, including the coordinated loss of the nuclear lamina (NL) and the histones, supports the involvement of the NL in spermatid nuclear remodelling, but how the NL links to the chromatin is not known. In somatic cells, interactions between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 51 publications
4
28
1
Order By: Relevance
“…Similar to LAP2 structure, LEMD1 is composed of a large nucleoplasmic domain comprising the LEM motif at the N‐terminus, a single transmembrane domain and a short perinuclear domain at the C‐terminus (Wagner & Krohne, ; Barton, Soshnev & Geyer, ). The expression of this NE protein is largely restricted to the testis, where six alternatively spliced isoforms can be found (Yuki et al ., ), and it is thought to have a role in chromatin remodelling during spermiogenesis (Table ; see Section III.2) (Elkhatib et al ., ).…”
Section: Nuclear Envelope Proteins Relevant To Mammalian Spermatogenesismentioning
confidence: 97%
See 4 more Smart Citations
“…Similar to LAP2 structure, LEMD1 is composed of a large nucleoplasmic domain comprising the LEM motif at the N‐terminus, a single transmembrane domain and a short perinuclear domain at the C‐terminus (Wagner & Krohne, ; Barton, Soshnev & Geyer, ). The expression of this NE protein is largely restricted to the testis, where six alternatively spliced isoforms can be found (Yuki et al ., ), and it is thought to have a role in chromatin remodelling during spermiogenesis (Table ; see Section III.2) (Elkhatib et al ., ).…”
Section: Nuclear Envelope Proteins Relevant To Mammalian Spermatogenesismentioning
confidence: 97%
“…In this study, testis‐specific LEMD1 was also found to exhibit an atypical nucleoplasmic localization in human post‐meiotic male germline cells, in which it is excluded from the acrosomal area of early round spermatids and progressively concentrates at the posterior region from late round spermatids to elongated spermatids, disappearing in mature spermatozoa (Table ; Fig. ) (Elkhatib et al ., ). Similarly, LAP2, presumably the β isoform, was reported to be initially present at the nuclear periphery of human early round spermatids and to gradually relocate to the nucleoplasm until spermatid elongation is initiated, when it is no longer detectable (Table ) (Elkhatib et al ., ).…”
Section: Nuclear Envelope Proteins Relevant To Mammalian Spermatogenesismentioning
confidence: 97%
See 3 more Smart Citations